Evaluation of particulate emission from a Palm Oil Mill Boiler - M. Rashid, Rashid; W.C., Chong; M. Ramli, Ramli; Z.N. Zainura, Zainura; J. Norruwaida, Norruwaidaaida (Universiti Kebangsaan Malaysia, 2013)
A study to investigate the particulate emission from a boiler of a palm oil mill plant equipped with a multi-cyclones particulate arrestor was performed and reported in this paper. The particulate emission concentration was measured at the outlet of an 8000 kg steam/h capacity water-tube typed boiler of a palm oil mill plant processing 27000 kg/h of fresh fruit bunch (FFB). The particulate sample was collected iso-kinetically using the USEPA method 5 sampling train through a sampling port made at the duct of the exiting flue gas between the boiler and a multi-cyclones unit. The results showed that the particulate emission rates exiting the boiler varied from 8.51 g/s to 126 g/s with an average of 44.3±31.6 g/s. In terms of concentration, the average particulate emission concentration exiting the boiler was 7.75±4.71 g/Nm3 (corrected to 7% oxygen concentration), ranging from 1.50 to 17.7 g/Nm3 (@7% O2) of the flue gas during the measurement. Based on the 27000 kg/h FFB processed, 6000 kg/h fiber and shell (F&S) burned and the capacity of the boiler of 8000 kg steam/h, the calculated particulate emission factor was 5.91±4.21 g particulate/kg FFB processed, 26.6±18.9 g particulate/kg F&S burned and 19.9±14.2 g particulate/kg boiler capacity, respectively. Based on the finding, in order to comply with the emission limits of 0.4 g/Nm3, the required collection efficiency of any given particulate pollution control system to consider for the mill will be between 73 and 98%, which is not easily achievable with the existing multi-cyclones unit.